Kierkegaard on the eternal validity of the self - Powell, Brian K. (International journal of philosophy and theology, 2015)
The mysterious phrase, ‘the eternal validity of the self,’ is clearly quite important in Kierkegaard’s pseudonymous works. A reader of those works will see that becoming aware of your eternal validity is a prerequisite for becoming both Judge William’s ‘ethical man’ and Johannes de Silentio’s ‘knight of faith,’ but the same reader is likely to be unsure just what it means to become aware of yourself in your eternal validity. In this paper, I discuss and critique various accounts of the concept of the eternal validity of the self. Then, I offer an account of that notion which proceeds from careful attention to Judge William’s use of the phrase in Either/Or. Finally, I connect my account with some of Kierkegaard’s writings beyond Either/Or.